qaḍiyyah al-ḥūriyīn bi-’ilāqatihim ma‘a madīna Kaḥat (Tall Ваrrī) mu‘ṭiyyāt ǧadīdah - Sālfīnī, Māryū
Text irrtümlich: s’l?yny; ersch. 1986?; Mirjo Salvini; The Problem of the Hurrians in their Relationship with the City of Ka?at (Tell Barri): New Facts; in Arabic, translated and abridged by Baš?r Zuhd?.